Relationship between Board Characteristics and Performance of Listed Companies of the Market for Alternative Investment - Promtong, Nantiya (KKBS Journal of Business Administration and Accountancy, 2020)
The objective of this study is to examine the relationship between board characteristics and performance of listed companies of the Market for Alternative Investment (MAI). Board characteristics independent variables used in this study are board size, board independence, CEO duality, and CEO family. Firm performances used in this study are accounting-based performance and market-based performance. Completely, 139 firms were chosen as a sample of the study. Secondary data was gathered via SETSMART database, and then analyzed using inferential statistic that is multiple regression analysis. The results of this study demonstrate that board size, board independence, and CEO family have no significant effect on both aspect of firm performance. Besides, CEO duality has negative significant effect on both aspect of firm performance. Further, CEO's independence board member has negative significant effect on market-based performance.